Partidos políticos, fidelidade obrigatória e coligações: as tensões pela titularidade do mandato eletivo no Brasil - SILVA, José Renato de Oliveira (Universidade Federal do Pará, 2017)
The party loyalty as a condition for the exercise of elective offices in Brazil was expressed in the previous constitutional order, 1967, incorporated by Constitutional Amendment nº. 1, 1969. The present Federal Constitution of 1988, in turn, made no mention of such a requirement, so repeatedly by the Supreme Court, urged to speak out about the institute's survival, answered negatively, saying not find constitutional den loss of elective office by party affiliation. In 2007 the jurisprudential evolution has led to the opposite conclusion, initially by the Superior Electoral Court to answer to Consultations 1.398 and 1.407, and then by the Supreme Court to decide the Writs of Mandamus 26.602, 26.603 and 26.604. It is established then that the ownership of elective offices is of political parties, not the candidates elected for them, either through the majority system or the proportional system, and as a result was issued by the TSE Resolution 22.610/2007 disciplining loss mandate by party affiliation, despite there had been no constitutional or infra-constitutional change in this regard. In May 2015 the Supreme Court excluded from the mandatory party loyalty rule elected by the majority system (the Executive’s leaders and senators), again without there being any constitutional or infra mutation. Remained current rule regarding elected by proportional system. Only in September 2015 the National Congress approved and the President signed and has recently published Law No. 13,165, which finally came expressly provide for the loss of office by causeless party affiliation. This is another chapter, unfinished as it is still pending regulation by the TSE and especially the interpretation by the Supreme Court, a kind of political reform hitherto shaped by a moot judicial activism. The first line of research in this paper is whether the party loyalty as a requirement for the exercise of elective office, that of the primordial teleological rule that the endowment of this mandate is indeed the party, not the person elected, is not in contradiction with the possibility of several associations colligate, only temporarily and regardless of their ideologies, to contest a particular election in a situation that can possibly intended for office to come wander the diverse party, though connected. Another line of investigation is whether Brazilian courts would not be going beyond its constitutional mission and promoting a kind of judicialization politics to establish in 2007 the possibility of elective office loss by party infidelity, radically altering its established case law since the enactment of the Charter Policy 1988, and that to do so would compete without any legislative developments, let alone constitutional amendment. The method used is the bibliographic, based on historical research, law, doctrine and jurisprudence. The results pointed to the incompatibility of fidelity institutes and coalitions, as well as a growing judicial activism and consequent judicialization of politics by which spends Brazil.